(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article is aimed at studying the influence of mass media, in particular media, on the physical education of young people. The key components of the concept under study and their interrelation through the prism of research of leading didactics are highlighted: physical education, mass media, media, propaganda, information. The role of media in forming interest in physical activity and sports among the younger generation is revealed. Various types of media, such as television, radio, and the Internet, are analyzed, as well as their capabilities in the context of promoting a healthy lifestyle and Physical Culture. The article examines the positive and negative aspects of the influence of media on physical education, as well as identifies prospects for optimizing this interaction in order to increase the activity and interest of young people in a healthy lifestyle. Attention is focused on the educational potential of using mass media, in particular media, in the physical education of young people, which opens up broad prospects for attracting attention and attracting the younger generation to a healthy lifestyle. The article analyzes the ways of media influence on the consciousness of young people in order to promote physical education and a healthy lifestyle: highlighting the importance of physical activity through the media; using games and applications for physical activity; broadcasting sports events and competitions; virtual training and instructions; creating online resources for physical activity. The research is based on current scientific approaches that reflect trends in changes in the physical education of young people under the influence of media in the modern Information Society. The authors draw conclusions and recommendations on the effective use of media to promote a healthy lifestyle and maintain physical activity among young people.